Tween® Preserves Enzyme Activity and Stability in PLGA Nanoparticles - Jason Thomas Duskey (MDPI AG, 2021)
Enzymes, as natural and potentially long-term treatment options, have become one of the most sought-after pharmaceutical molecules to be delivered with nanoparticles (NPs); however, their instability during formulation often leads to underwhelming results. Various molecules, including the Tween® polysorbate series, have demonstrated enzyme activity protection but are often used uncontrolled without optimization. Here, poly(lactic-co-glycolic) acid (PLGA) NPs loaded with β-glucosidase (β-Glu) solutions containing Tween® 20, 60, or 80 were compared. Mixing the enzyme with Tween® pre-formulation had no effect on particle size or physical characteristics, but increased the amount of enzyme loaded. More importantly, NPs made with Tween® 20:enzyme solutions maintained significantly higher enzyme activity. Therefore, Tween® 20:enzyme solutions ranging from 60:1 to 2419:1 mol:mol were further analyzed. Isothermal titration calorimetry analysis demonstrated low affinity and unquantifiable binding between Tween® 20 and β-Glu. Incorporating these solutions in NPs showed no effect on size, zeta potential, or morphology. The amount of enzyme and Tween® 20 in the NPs was constant for all samples, but a trend towards higher activity with higher molar rapports of Tween® 20:β-Glu was observed. Finally, a burst release from NPs in the first hour with Tween®:β-Glu solutions was the same as free enzyme, but the enzyme remained active longer in solution. These results highlight the importance of stabilizers during NP formulation and how optimizing their use to stabilize an enzyme can help researchers design more efficient and effective enzyme loaded NPs.